(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2007)
Categorization of verbalizations of the therapeutic process can to be interpreted as intraverbal training. Thus, evaluation of the variables involved in this training would give us information about relevant variables of categorization activity. This work analyzed the procedures and results of the studies using the training of intravebal responses, aiming to identify relevant variables in intraverbal behavior acquisition, and therefore in categorization. The following variables were identified: presence of textual cues; use of examples (especially the exposure to a procedure of multiple examples instruction) and, in the context of the instructional relations, both exposure to definition tasks before starting example identification tasks and identification of the concept’s keys aspects. These variables seem to be related directly to those identified in the studies about categorization of verbalizations of the therapeutic process, suggesting that they must be taken into account in the development of studies about this subject.